Agricultural Extension: Global Status and Performance in Selected Countries - Davis, Kristin E. (2021)
Kristin Davis SPECIAL EVENT UNFSS Independent Dialogue: The Critical Role of Agricultural Extension in Advancing the 2030 Agenda: Lessons from the Field and Empirical Evidence Co-Organized by IFPRI and Sasakawa Africa Association (SAA)